Contemporary ecotourism development from the perspective of traditional Taoist philosophy - Zhiluan Ma; Fang Li (Trans/Form/Ação)
The development of modern ecotourism cannot do without the support of the cultural industry. Placing China's ecotourism industry within the traditional Taoist ideology and culture of China can effectively establish a systematic cultural and tourism theory, enrich the methods of ecotourism construction and promote the development of the tourism industry. Therefore, this study is based on Taoist ecological ideology and analyzes the impact of traditional ideological connotations on the development of ecotourism from the perspectives of natural harmony and spiritual balance in Taoist ideology. At the same time, the study explores the modern value of Taoist philosophy and its advantages in integrating with tourism at three levels: sustainable development, social ecological civilization and human spiritual needs. The purpose of this study is to explore the development path of contemporary sustainable ecotourism culture and provide theoretical guidance for achieving harmonious development and unity between humans and nature.